Adjuvant therapy for endometrial cancer in the era of molecular classification: radiotherapy, chemoradiation and novel targets for therapy. Issue 4 (20th October 2020) - van den Heerik, Anne Sophie V M; Horeweg, Nanda; de Boer, Stephanie M; Bosse, Tjalling; Creutzberg, Carien L
Abstract : Endometrial cancer is primarily treated with surgery. Adjuvant treatment strategies for endometrial cancer, such as external beam pelvic radiotherapy, vaginal brachytherapy, chemotherapy, and combined chemotherapy and radiotherapy, have been studied in several randomized trials. Adjuvant treatment is currently based on the presence of clinico-pathological risk factors. Low-risk disease is adequately managed with surgery alone. In high-intermediate risk endometrial cancer, adjuvant vaginal brachytherapy is recommended to maximize local control, with only mild side effects and without impact on quality of life. For high-risk endometrial cancer, recent large randomized trials support the use of pelvic radiotherapy, especially in stage I–II endometrial cancer with risk factors. For women with serous cancers and those with stage III disease, chemoradiation increased both recurrence-free and overall survival, while GOG-258 showed similar recurrence-free survival compared with six cycles of chemotherapy alone, but with better pelvic and para-aortic nodal control with combined chemotherapy and radiotherapy. Recent molecular studies, most notably the work from The Cancer Genome Atlas (TCGA) project, have shown that four endometrial cancer molecular classes can be distinguished; POLE ultra-mutated, microsatellite instable hypermutated, copy-number-low, and copy-number-high. Subsequent studies, using surrogate markers to identify groups analogous to TCGA sub-classes, showed that all four endometrial cancer sub-types are found across all stages, histological types, and grades. Moreover, the molecular sub-groups have proved to have a stronger prognostic impact than histo-pathological tumor characteristics. This introduces an new era of molecular classification based diagnostics and treatment approaches. Integration of the molecular factors and new therapeutic targets will lead to molecular-integrated adjuvant treatment including targeted treatments, which are the rationale of new and ongoing trials. This review presents an overview of current adjuvant treatment strategies in endometrial cancer, highlights the development and evaluation of a molecular-integrated risk profile, and briefly discusses ongoing developments in targeted treatment.